Criminal Compensation in State Loss Recovery: A Legal Sociological Analysis of Public Response on Social Media - Lisda Ariany; Masithoh Masithoh; Abdurahman Syayuthi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Criminal compensation is normatively intended as an instrument for recovering state losses caused by corruption. However, in practice, its implementation is often considered ineffective in achieving substantive justice and creating a deterrent effect. This study analyzes the role of criminal compensation in recovering state losses from a legal sociology perspective. It focuses on two issues: public responses on social media to compensation orders in corruption cases and the extent to which these responses reflect the social legitimacy of compensation as a legal instrument for state loss recovery. The research employs an empirical juridical method with a sociological approach. Data were collected from the X/Twitter platform, covering discussions on compensation sanctions in corruption cases during January–October 2025. The dataset consisted of 420 tweets, complemented by relevant online news reports and supporting documents. Data were analyzed using content analysis and word cloud techniques to identify dominant public sentiments. The findings reveal a predominance of negative public sentiment toward the implementation of compensation sanctions. Public criticism is mainly associated with perceptions of legal inequality, declining trust in law enforcement institutions, and the limited deterrent effect of compensation penalties, particularly when accompanied by lenient prison sentences or political interventions such as amnesty and abolition for corrupt offenders. From a legal sociology perspective, these perceptions indicate weak normative legitimacy of the legal system in fulfilling its justice function. The study recommends enhancing transparency in determining compensation amounts, integrating compensation sanctions with additional penalties, strengthening public oversight of judgment execution, and improving mechanisms for corruption asset recovery.